Effect of donor exclusion criteria on blood safety and volume of donations: a systematic review of modelling studies. - Mosselmans, Luce; Janssen, Mart P.; Feys, Hendrik B.; de Buck, Emmy; Schiltz, Fritz; Vandenberghe, Peter; Vandekerckhove, Philippe; Van Remoortel, Hans (Bulletin of the World Health Organization, 2026)
Objective To assess the effect of easing bans and deferral policies on blood donation from men who have sex with men on blood safety and volume from modelling studies. Methods We searched four databases (PubMed®, Embase®, CINAHL and Web of Science) for modelling studies on the impact of replacing bans or deferrals on blood donations from men who have sex with men with shorter deferral periods or no deferrals. We synthesized and compared findings from the different modelling studies, and assessed risk of bias and certainty of evidence. Findings Fourteen publications were included in the study. All the studies estimated the human immunodeficiency virus (HIV) residual risk of an HIV-infected blood donation being received, going undetected through screening and entering the blood supply. Despite medium to large increases in risks (up to three-fold) in relaxing donor policies for men who have sex with men, the absolute HIV residual risk remained very low in all scenarios, ranging between 0.05 and 1.1 HIV-positive units per million donations. The increase in donors ranged from 0.04% to 2.10%. No models covered other transfusion-transmissible infections such as syphilis or hepatitis C. Conclusion Modelled HIV residual risk estimates increased slightly with relaxed policies on donations from men who have sex with men. However, differences in risk and blood volume estimates between different policies are generally very small. To support decisions on easing donor policies for men who have sex with men, models should also quantify residual risks for non-HIV transfusion-transmissible infections, such as syphilis.